Konseling Parenting sebagai Media Dakwah Preventif dalam Mengatasi Krisis Kesehatan Mental Remaja di Kota Bandung - Santika Pebrianti, Natasya (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2015)
Family or parents are an important factor in parenting, the phenomenon of parental attitudes in implementing parenting is still very sensitive in terms of protecting teenagers' mental health. The aim of this research is to determine the implementation of the program, process and results of parenting counseling carried out by PUSPAGA Bandung City in overcoming inappropriate parenting patterns. This study used descriptive qualitative method. The results of this research conclude that PUSPAGA Bandung City programs and activities in the process of implementing parenting counseling services use several approaches, namely, Client Centered Therapy, Rational Emotive Therapy and family group therapy," which shows that the dominant parenting style should ideally use varied parenting patterns in Maximum formation of children's psychological character.